Exploring structural breaks in the economic-financial nexus evidence from panel data analysis - Diana Hassan; Assis Kamu; Ricky Chee Jiun Chia; Ho Chong Mun (ResearchGate, 2024)
This study investigates the response of panel data consisting of the ASEAN-5 stock market to selected macroeconomic variables from January 2012 to December 2022. Specifically, it analyzes industrial production, the consumer price index, money supply (M1), Treasury Bills, long-term interest rates, and exchange rates. Utilizing the panel data approach, this research identifies two recent crises: U.S. Stock Market Crashes and the COVID-19 pandemic. The panel regression analysis reveals that the ASEAN-5 stock market index is consistently influenced by two different sets of selected macroeconomic variables. The results from Panel I indicate that industrial production and Treasury Bills have a negative influence, the consumer price index has a positive influence, and there is a mixed effect for money supply across the two breaks. When considering the long-term interest rate in Panel II, the results suggest the same selected variables and directional influence as seen on Panel I affecting the ASEAN-5 stock market. These findings remain consistent even after detecting structural breaks and conducting diagnostic checks. They also align with the observation that markets in developed economies tend to be heightened responsiveness to crises and global conflicts.